Effects of Asian cultural values on parenting style and young children’s perceived competence: A cross-sectional study - Yim, Eunice Pui-Yu (Frontiers in Psychology, 2022)
Authoritarian parenting has long been associated with Western individualism and improved child development. This study examined the relationship between cultural values, parenting styles, and children’s perceived competence in Hong Kong. A total of 48 parents from local Chinese families, 49 parents from South Asian families, and 105 children (24 local Chinese and 81 South Asian) aged 5–6 years participated in the study. Self-report questionnaires on adherence to Asian cultural values and parenting style were administered to parents. The Pictorial Survey on Children’s Perceived Competence was administered to children by trained research assistants. The results contradicted two long-standing assumptions on Asian cultural values and parenting styles. First, higher adherence to Asian cultural values increased the likelihood of having an authoritarian parenting style. Second, authoritative parenting practices were more likely be associated with improved social-emotional competence in children. Multiple regression analyses revealed a strong positive correlation between Asian cultural values and authoritative parenting style (R2 = .597). There was no association between parenting style and the development of competence in young children. However, a positive correlation was found between Asian cultural values and young children’s perceived competence. This study showed that components of collectivism and humility in Asian cultural values could have functional values that are essential for developing competencies in South Asian young children but not in local Chinese young children. This study discussed the implications of cultural values sin the terms of contextualization, functional relevance of cultural values for ethnic minorities, and ideal parenting practices.